On the physiology of jouissance: interpreting the mesolimbic dopaminergic reward functions from a psychoanalytic perspective - Bazan, Ariane; Detandt, Sandrine (Frontiers in Human Neuroscience, 2013)
Jouissance is a Lacanian concept, infamous for being impervious to understanding and which expresses the paradoxical satisfaction that a subject may derive from his symptom. On the basis of Freud’s “experience of satisfaction” we have proposed a first working definition of jouissance as the (benefit gained from) the motor tension underlying the action which was [once] adequate in bringing relief to the drive and, on the basis of their striking reciprocal resonances, we have proposed that central dopaminergic systems could embody the physiological architecture of Freud’s concept of the drive. We have then distinguished two constitutive axes to jouissance: one concerns the subject’s body and the other the subject’s history. Four distinctive aspects of these axes are discussed both from a metapsychological and from a neuroscience point of view. We conclude that jouissance could be described as an accumulation of body tension, fuelling for action, but continuously balancing between reward and anxiety, and both marking the physiology of the body with the history of its commemoration and arising from this inscription as a constant push to act and to repeat. Moroever, it seems that the mesolimbic accumbens dopaminergic pathway is a reasonable candidate for its underlying physiological architecture.